The Effect of Financial Literacy and other Determinants on the Intention to Use Electronic Money: Consumer Behavior as a Variable Mediation - Shinta Heru Satoto; Hasa Nurrohim Kurniawan Putra (International Journal of Applied Business and International Management, 2021)
The purpose of this study is to investigate how financial literacy and other determinants affect the intention to use electronic money with consumer behavior as a mediating variable. The other determinants are financial capabilities, perceived benefits, and perceived ease of use. The data were collected by distributing questionnaires and analyzed using path analysis. The findings indicate financial literacy, financial capability, perceived benefits, and perceived ease of use directly influence the intention to use electronic money. Moreover, consumer behavior is able to mediate the influence of financial literacy, financial capability, and perceived ease of use, yet unable to mediate the effect of perceived benefits on intention to use electronic money.